2023
DOI: 10.3390/plants12071524
|View full text |Cite
|
Sign up to set email alerts
|

Review on Rice Husk Biochar as an Adsorbent for Soil and Water Remediation

Abstract: Rice husk biochar (RHB) is a low-cost and renewable resource that has been found to be highly effective for the remediation of water and soil environments. Its yield, structure, composition, and physicochemical properties can be modified by changing the parameters of the preparation process, such as the heating rate, pyrolysis temperature, and carrier gas flow rate. Additionally, its specific surface area and functional groups can be modified through physical, chemical, and biological means. Compared to biocha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 159 publications
0
3
0
Order By: Relevance
“…In this regard, carbonized rice husk has been extensively studied under a limited supply of oxygen (O 2 ) and at moderate pyrolysis temperatures to enhance its calorific value, carbon content, and pore properties in recent years [16][17][18][19][20][21][22][23]. The biochar produced from rice husk can be used as soil amendment, liquid-phase adsorbent, or as a precursor for activated carbon [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, carbonized rice husk has been extensively studied under a limited supply of oxygen (O 2 ) and at moderate pyrolysis temperatures to enhance its calorific value, carbon content, and pore properties in recent years [16][17][18][19][20][21][22][23]. The biochar produced from rice husk can be used as soil amendment, liquid-phase adsorbent, or as a precursor for activated carbon [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Cd, minimum adsorption percentages can be seen when using the biosorbent URH, obtaining up to 20% adsorption when using URH1. However, when using RHTA1, it is observed that this percentage increased to 40%, probably as a consequence of the greater number of functional groups exposed and with which this metal can interact, since it is known that the functional groups that contain nitrogen have a strong affinity for the formation of complexes with metals, such as Cd, Cu, and Zn [60].…”
Section: Adsorption and Desorption Of Metalsmentioning
confidence: 99%
“…which this metal can interact, since it is known that the functional groups that contain nitrogen have a strong affinity for the formation of complexes with metals, such as Cd, Cu, and Zn [60]. In addition, it is important to point out that the pH plays an important factor; therefore, in this study, the pH was 5, which favors the adsorption of these metal ions, because if the pH is increased, the surface of the biosorbent becomes in a higher positive charge that promotes a slow removal of metal ions [12].…”
Section: Adsorption and Desorption Of Metalsmentioning
confidence: 99%